Long-term preservation of functional capacity and quality of life in advanced heart failure patients with bridge to transplant therapy: A report from Japanese nationwide multicenter registry. (1st June 2022) - Sato, Takuma; Kobayashi, Yuta; Nagai, Toshiyuki; Nakatani, Takeshi; Kobashigawa, Jon; Saiki, Yoshikatsu; Ono, Minoru; Wakasa, Satoru; Anzai, Toshihisa
Abstract: Background: Under the revised heart allocation system in the United States, bridge to transplant (BTT) patients with left ventricular assist device (LVAD) have a longer waitlist period, as they are now lowly prioritized. However, little is known regarding the long-term trajectory of functional capacity (FC) and health-related quality of life (HR-QOL) among BTT-LVAD patients. Methods: We retrospectively analyzed 442 consecutive patients with BTT-LVAD between April 2013 and May 2019 from a Japanese nationwide registry. FC (New York Heart Association [NYHA] functional class, peak oxygen uptake [VO2 ], and 6-min walk test [6MWT]) and HR-QOL (European Quality of Life [EQ-5D index] and Visual Analogue Scale [EQ-VAS]) were assessed at baseline and for up to 60 months after LVAD implantation. Results: During the follow-up period of 30 months (IQR 18–42 months), 100 (22.6%) patients underwent transplantation, 37 (8.3%) died, and 14 (3.1%) underwent explantation for recovery. Mean peak VO2, 6MWT distance, EQ-5D index, and EQ-VAS significantly improved 3 months after LVAD implantation ( p = 0.0012, p = 0.0037, p < 0.001, p < 0.001, respectively). Furthermore, these improvements were sustained for up to 60 months following LVAD implantation. Major adverse events including device failure, infection, stroke, and bleeding, which occurred within the first 3 months after LVAD implantation may have not affected FC or HR-QOL for up to 60 months ( p = 0.15, p = 0.22, respectively). Conclusions: BTT patients showed long-term preservation of FC and HR-QOL, suggesting that BTT remains an option despite the long waiting time to HTx. Highlights: BTT-LVAD patients showed long-term preservation of functional capacity and HR-QOL. Early major adverse events may have not affected long-term functional capacity or HR-QOL. This study suggested that BTT remains an option despite the long waiting list time.